ANALISIS PENGARUH INVESTMENT OPPORTUNITY SET, CASH CONVERSION CYCLE DAN CORPORATE GOVERNANCE STRUCTURE TERHADAP CASH HOLDINGS - Senjaya, Sheryl Yuliana; Yadnyana, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.08. TAHUN 2016, 2016)
The purpose of this study is to get empirical evidence about the influence of investment opportunity set, cash conversion cycle and corporate governance structure of the cash holdings. The population in this study using secondary data on the company's property and real estate sectors which are listed on the Indonesia Stock Exchange period 2008 to 2014. Sampling was done by purposive sampling method with the samples obtained as many as 34 companies. This study using multiple regression analysis model on testing the hypothesis. The analysis showed investment opportunity set (IOS) as measured by MBVA affect positively on cash holdings, the results of hypothesis testing in accordance with the pecking order theory which states that a high level of IOS which will create demand for the supply of high cash. The analysis also shows that the size of the board of commissioners had positive effect on cash holdings which indicates that the board size small facilitate control and accelerate decision-making, so that commissioners can act faster and easier to monitor management actions that can act according to its own interests. While the analysis showed that cash conversion cycle, independent directors and institutional ownership has no effect on cash holdings
Keywords: Cash Holdings, Investment Opportunity Set, Cash Conversion Cycle, Corporate Governance